Enhancing mathematical problem-solving skills: The impact of the SSCS learning model integrated with GeoEnzo - Putra, Fredi Ganda; Widyawati, Santi; Imama, Khoirunnisa; Arditha, Restiya (Indonesian Journal of Science and Mathematics Education, 2025)
Many students in Indonesia continue to experience difficulties in mathematical problem-solving due to the persistent dominance of conventional teaching approaches that limit student engagement and creativity. This study examines the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model integrated with GeoEnzo in improving students’ mathematical problem-solving abilities. A quasi-experimental design with a posttest-only control group was employed. Seventh-grade students from SMPN Terpadu Gunung Pelindung, East Lampung, Indonesia, were selected through cluster random sampling. Data were collected using a validated mathematical problem-solving test and analyzed using one-way ANOVA and Scheffe’s multiple comparison test to identify differences in performance among the four instructional approaches. The SSCS model integrated with GeoEnzo yielded the highest mean score (88.31), followed by the SSCS model without GeoEnzo (83.56), the conventional model with GeoEnzo (83.03), and the traditional model without technological support (77.08). ANOVA results indicated statistically significant differences (Sig. = 0.000) among the groups. The findings confirm that integrating SSCS with GeoEnzo effectively enhances students’ mathematical problem-solving skills. This research has implications for encouraging educators and curriculum developers to adopt a student-centered, technology-based learning approach to enhance higher-order thinking skills.